Pengertian Dan Hakikat Pendidikan Multikultural - Zahra, Siti; Albina, Meyniar (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Multicultural education is a process of developing all human potential that respects plurality and heterogeneity as a consequence of cultural, ethnic, tribal and (religious) diversity. Multicultural education emphasizes a philosophy of cultural pluralism in an education system that is based on the principles of equality, mutual respect and acceptance as well as understanding and a moral commitment to social justice. Multicultural education began with the development of ideas and awareness about interculturalism after World War II. The emergence of the idea and awareness of interculturalism is not only related to developments in international politics regarding human rights, independence from colonialism, racial discrimination, etc., but also because of the increasing plurality in Western countries themselves as a result of increasing migration from newly independent countries to America. and Europe. Multicultural education is actually an attitude of "caring" and wanting to understand (difference) or "politics of recognition" the politics of recognizing people from minority groups. Multicultural education looks at society more broadly. Based on the basic view that attitudes of "indifference" and "non-recognition" are not only rooted in inequality racial structure, but the multicultural education paradigm includes subjects regarding injustice, poverty, oppression, and underdevelopment of minority groups in various fields: social, cultural, economic, educational, and so on. The aim of Islamic education is not just to fill students’ minds with knowledge and subject matter, but to cleanse their souls, which must be filled with good morals and values ​​and conditioned so that they can live a good life. This is in accordance with the aim of multicultural education, namely to create a harmonious life in a pluralistic society. Thus in essence, in a broad context, multicultural education seeks to unite the nation democratically, by uniting differences into advantages that can be appreciated in the world of education.